Dowling-Degos Disease Presenting Primarily with Comedones and Atrophic Scarring - Bianca M. Tod; Ilana Steenkamp; Henry Francois Jordaan; Willem I. Visser (MDPI AG, 2019)
Dowling-Degos disease (DDD) is a rare genodermatosis primarily presenting with reticulated pigmentation of the flexures. Secondary features include comedones and atrophic scarring. We present a patient with histologically confirmed DDD whose predominant clinical finding was of comedones and scarring, with less prominent pigmentation, thus expanding the clinical spectrum of DDD.